Design and Synthesis of New Steroid-Oxazin Derivative Using Some Strategies - Lauro, Figueroa-Valverde; Francisco, Diaz-Cedillo; Elodia, Garcia-Cervera; Eduardo, Pool-Gomez; Marcela, Rosas-Nexticapa; Maria, Lopez-Ramos; Lenin, Hau-Heredia; Betty, Sarabia-Alcocer (Asian Journal of Chemistry, 2014)
In this study, a steroid-oxazin derivative was synthesized using several strategies; the first stage involve the reaction of b-naphthol with ethylenediamine in presence of formaldehyde to form the compound 3 (3-(1H-naphtho[1,2-e][1,3]oxazin-2(3H)-yl)propan-1-amine). The second stage was achieved by reaction of 3 with dehydroisoandrosterone 3-sulfate to form the compound 5 (10,13-dimethyl-17-[2-(1H-naphtho[1,2-e][1,3]oxazin-2-yl)-ethylimino]-2,3,4,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-1H-cyclopenta[a]phenanthrene-3-sulfonic acid) using boric acid as catalyst. Finally, the third stage involve the synthesis of 17-{(3-chloro-2-oxo-cyclobutyl)-[2-(1H-naphtho[1,2-e][1,3]oxazin-2-yl)-ethyl]amino}-10,13-dimethyl-2,3,4,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-1H-cyclopenta[a]phenanthrene-3-sulfonic acid (7) by reaction of 5 with chloroacetyl chloride in presence of triethylamine. The structure of compounds obtained was confirmed by elemental analysis, spectroscopy and spectrometry data. In conclusion, this method offers some advantages such as good yields, simple procedure, low cost and ease of workup.